Development of hydroxyapatite-polylactic acid composite bone fixation plate - Komgrit Leksakul (2018)
© 2017 Walter de Gruyter GmbH, Berlin/Boston. Bone damage patients may suffer from metal toxicity resulting from an adverse reaction. To avoid the need for a second operation, we set out to identify a material that can be used as a substitute for metal in small fragment plates, which is compatible with the human body. Thus, in this study, we set out to study the development of a material that can be applied to the small fragment plate, based on a hydroxyapatite (HA)-polylactic acid (PLA) composite. This study examined three main factors, namely, the ratio of the PLA to the HA, injection temperature (T) and injection pressure (P). Based on the ASTM standard, the best results (Code 4 and Code 1) obtained from the mechanical property tests (tension and flexural) were 44.02 MPa and 63.97 MPa, respectively. When compared to HA-HDPE, our material offers both strength and biodegradable/biocompatible advantages. By inspection with scanning electron microscope (SEM) and energy-dispersive spectrometry (EDS), we could identify the components of the HA and distribution pattern. In terms of biocompatibility, Code 1 is promising. To maximize the composite desirability, optimal condition was mathematically calculated. In addition, finite element analysis confirmed that the proposed bone fixation plate would not be damaged when the wrist is impacted.